Characterizing rural food environments in South Asia - Choudhury, Samira; Srivastava, Amit; Bi, Afrin Zainab; Yeggina, Pavan Kumar; Veettil, Prakashan Chellattan (2022)
AFSSA (Transforming Agrifood Systems in South Asia), a CGIAR Regional Integrated Initiative, addresses food system challenges by delivering actionable evidence and scalable innovations in South Asia. This brief provides an overview of TAFSSA’s study on "Characterizing the rural food environments in South Asia”. The evidence generated from this study would promote reshaping of rural food environments to improve access to affordable nutritious foods in rural South Asia.